El nuevo Plan de Ayutla. Génesis de las autodefensas guerrerenses (1998-2013). Libro de Pierre Gaussens (2020) - Fuentes Díaz, Antonio (El Colegio de México, 2022)
The book analyzes the emergence of community defense groups in Ayutla de los Libres, Guerrero, as a reaction to the context of violence. Their emergence was triggered by structural modifications and historical processes that transformed social relations due to the change in state protection of peasant sectors, the growing importance of the municipal structure, and the appearance of a new type of violence linked to organized crime. The self-defense movement in Guerrero constitutes both a break from and a continuation of the guerrilla movements that have emerged in that region with new characteristics and expressions. This makes it possible to open the discussion on novel forms of statehood, in which armed defense responses gain fresh prominence.